2019 IEEE 15th International Conference on Automation Science and Engineering (CASE) 2019
DOI: 10.1109/coase.2019.8843327
|View full text |Cite
|
Sign up to set email alerts
|

Computational Effort of BDD-based Supervisor Synthesis of Extended Finite Automata

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This synthesis algorithm is based on the algorithm introduced in [20]. The application of BDDs in this algorithm is studied in [21], [22]. We have split up the algorithm over multiple algorithms to enable reuse of parts later.…”
Section: Symbolic Supervisor Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…This synthesis algorithm is based on the algorithm introduced in [20]. The application of BDDs in this algorithm is studied in [21], [22]. We have split up the algorithm over multiple algorithms to enable reuse of parts later.…”
Section: Symbolic Supervisor Synthesismentioning
confidence: 99%
“…For symbolic supervisor synthesis, the computational effort can be expressed by peak used BDD nodes and BDD operation count [21]. The first metric is the maximal combined size of all BDDs during synthesis.…”
Section: A Measuring Computational Effortmentioning
confidence: 99%
See 2 more Smart Citations
“…Their sizes are very sensitive to the ordering of systems variables against which they are constructed. In [39], it was shown that the difference between the 'right' and 'wrong' ordering for the variables in Lock III can mean a shift in computation time from a few seconds to a few hours. Initial results show that ordering variables based on a DSM can yield a significant compaction of binary decision diagrams.…”
Section: Research Challengesmentioning
confidence: 99%